SOCIAL CLASS AND FAMILY ENVIRONMENT QUALITY IN CHILDHOOD - Viguer Seguí, Paz; Serra Desfilis, Emilia (Anales de Psicología / Annals of Psychology)
The aim of this study is to analyse the relation between the family environment quality in childhood and the social class. For this one we have applied the H.O.M.E. Scale (Home Observation for Measurement of Environment) in the spanish versions, adapted by Moreno and Palacios in 1990 and 1992 respectively, to a sample of 410 children, both sex and ages between 3 and 10. Results show that the social class where children are developted, is a higtly significant aspect in the family environment, making an important relation with quality of that. From early years important differences in the quality of familiar environment exist, for this one at social level is important working in the compensation of this structural inequalities with a children education and others quality community iniciatives, that promove and give ambients, materials and stimulate experiences of child development.